PELAKSANAAN EKSEPSI TERHADAP SURAT DAKWAAN DALAM PROSES PERKARA PIDANA DI PENGADILAN NEGERI BULUNGAN - Edison, Edison (Universitas 17 Agustus 1945 Samarinda, 2018)
ABSTRACTIn the proceedings of the session of the District Court, that is, after being completed in a courtroom consisting of a single Judge or Judge of the Assembly, the Prosecutor / Prosecutor, the Clerk and the Defendant and or accompanied by his legal counsel. Then the trial of the case is announced by the Judge or the Chief Justice of the Assembly declaring that the hearing is opened declared open to the public and / or closed, with the systematic event as follows: The prosecutor is welcome to read the indictment before the defendant; Witness examination; The examination of the defendant; Requisitoir Prosecutor; Pledoi from the Legal Counsel; Replication of the Prosecutor; Duplication from the Legal Counsel; Decision. The exception is actually less effective, since almost every defendant or his legal counsel who filed an exception may be rejected by the Judge at a first instance court. This is because before the trial begins, the Prosecutor may request judgment to the Judge and the Prosecutor may change the indictment before the trial begins. And if the exception is rejected then the case continues. And if the exception is accepted it does not mean the criminal case is over, because the decision of the exception is not a final decision. In the case of the decision of the exception, both the Prosecutor, the defendant and his legal advisor may file a resistance (verzet) or an appeal. And if the exception is accepted, the Prosecutor may make an indictment and send it back to the District Court.